2008
DOI: 10.1186/1478-4505-6-13
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and implementation of tobacco dependence treatment guidelines in Arizona: Healthcare Systems Survey 2000

Abstract: Background: This paper presents findings from the Tobacco Control in Arizona Healthcare Systems Survey, conducted in 2000. The purpose of the survey was to assess the status of Arizona healthcare systems' awareness and implementation of tobacco cessation and prevention measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The level of inter-rater agreement was computed and any differences resolved through discussion. The areas of tobacco control and obesity reduction were chosen because these are among the most important in public health and ones where health professional behaviour has consistently been found to fall short of that recommended by evidence-based guidelines [ 24 - 26 ]. In addition, these documents cover a wide spectrum of behaviour change approaches.…”
Section: Methodsmentioning
confidence: 99%
“…The level of inter-rater agreement was computed and any differences resolved through discussion. The areas of tobacco control and obesity reduction were chosen because these are among the most important in public health and ones where health professional behaviour has consistently been found to fall short of that recommended by evidence-based guidelines [ 24 - 26 ]. In addition, these documents cover a wide spectrum of behaviour change approaches.…”
Section: Methodsmentioning
confidence: 99%
“…Studies by Gillies et al(71), and others(37, 52) have shown a relationship between quality and use of systems using a related instrument. An interesting set of related findings was reported in a recent paper by Scholle(72), indicating a negative relationship between quality of care using HEDIS quality measures in diabetes and resource use measures of total utilization of inpatient, surgical and procedures by the same patients at the health plan level.…”
Section: Discussionmentioning
confidence: 95%